An Exploration in the Theory of Optimum Income Taxation - Mirrlees, J. A. (Review of Economic Studies, 1971)
Journal Article An Exploration in the Theory of Optimum Income Taxation Get access J. A. Mirrlees J. A. Mirrlees Nuffield College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 2, April 1971, Pages 175–208, https://doi.org/10.2307/2296779 Published: 01 April 1971